1995
DOI: 10.1037/0096-1523.21.4.901
|View full text |Cite
|
Sign up to set email alerts
|

Facial organization blocks access to low-level features: An object inferiority effect.

Abstract: The current study investigated the influence of a low-level local feature (curvature) and a high-level emergent feature (facial expression) on rapid search. These features distinguished the target from the distractors and were presented either alone or together. Stimuli were triplets of up and down arcs organized to form meaningless patterns or schematic faces. In the feature search, the target had the only down arc in the display. In the conjunction search, the target was a unique combination of up and down a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
119
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 36 publications
14
119
4
Order By: Relevance
“…3b Right). These results suggest that blindsight is exclusive for the expression signaled by the emoticon as a whole (24).…”
Section: Resultsmentioning
confidence: 64%
“…3b Right). These results suggest that blindsight is exclusive for the expression signaled by the emoticon as a whole (24).…”
Section: Resultsmentioning
confidence: 64%
“…In a recent study, Suzuki and Cavanagh (1995) compared visual search for a unique feature (e.g., down arc) when it was located in 6, 12, or 18 triplets of features (e.g., up arcs) arranged to form either faces or meaningless patterns. They found that visual search for the unique feature was less efficient, as was indicated by the slopes of the search functions, when the features were arranged to form faces.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that relatively complex types of visual information, such as perceived surfaces (He & Nakayama, 1992), item structure (Wolfe, 1996), orientations of objects (Enns & Rensink, 1991), familiarity of objects (Wang, Cavanagh, & Green, 1994), changes to objects (Smilek, Eastwood, & Merikle, 2000), and the global representation of a face (Suzuki & Cavanagh, 1995), can play a functional role in guiding focal attention. It is unclear, however, whether or not emotional expressions are also perceived outside the focus of attention and play a functional role in guiding attention.…”
mentioning
confidence: 99%
“…If it takes longer to reject B's than it does to reject A's, then search for A among B will be slower than search for B among A. For example, it can be harder to search for a "smile" curve among frowns when the critical curved line is embedded in a schematic face (Suzuki and Cavanagh, 1995). This slowing of search does not have to do with the absence of a feature but with the particularities of processing facelike stimuli.…”
Section: Looking For Preattentive Featuresmentioning
confidence: 95%